Chlamydomonas reinhardtii genetic variants as probes for fluorescence sensing system in detection of pollutants (2009)
ABSTRACT: The unicellular green alga Chlamydomonas reinhardtii is employed here for the setup of a biosensor demonstrator based on multibiomediators for the detection of herbicides. The detection is based on the activity of photosystem II, the multienzymatic chlorophyll–protein complex located in the thylakoid membrane that catalyzes the light-dependent photosynthetic primary charge separation and the electron transfer chain in cyanobacteria, algae, and higher plants. Several C. reinhardtii mutants modified on the D1 photosystem II protein are generated by site-directed mutagenesis and experimentally tested for the development of a biosensor revealing the modification of the fluorescence parameter (1−VJ) in the presence of herbicides. The A250R, A250L, A251C, and I163N mutants are highly sensitive to the urea and triazine herbicide classes; the newly generated F255N mutant is shown to be especially resistant to the class of urea. It follows that the response of the multibiomediators is associated to a particular herbicide subclass and can be useful to monitor several species of pollutants